2014
DOI: 10.4103/0971-3026.134400
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and magnetic resonance imaging in the evaluation of pelvic peritoneal adhesions: What radiologists need to know?

Abstract: Pelvic peritoneal adhesions constitute an important cause of concern which affects the life of millions of people worldwide due to complications like abdominal pain, bowel obstruction and infertility along with challenges in surgical exploration. Precise pre-operative diagnosis of the presence and extent of peritoneal adhesions is of great clinical and surgical importance. Diagnostic laparoscopy to detect peritoneal adhesions may itself lead to formation of adhesions. Routine CT and MRI studies are therefore u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…It is reported that 60% of small bowel obstructions are due to adhesions, with 80% of cases occurring after surgery [10]. Adhesive small bowel obstruction is seen in 3% of all laparotomies and can occur as early as within three days to two weeks, with 40% formed within one year [11]. Other causes of adhesion are inflammation, seen in 15% of cases, and rare cases are due to congenital or unexplained causes [10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 60% of small bowel obstructions are due to adhesions, with 80% of cases occurring after surgery [10]. Adhesive small bowel obstruction is seen in 3% of all laparotomies and can occur as early as within three days to two weeks, with 40% formed within one year [11]. Other causes of adhesion are inflammation, seen in 15% of cases, and rare cases are due to congenital or unexplained causes [10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive small bowel obstruction is seen in 3% of all laparotomies and can occur as early as within three days to two weeks, with 40% formed within one year [11]. Other causes of adhesion are inflammation, seen in 15% of cases, and rare cases are due to congenital or unexplained causes [10][11]. Pongpornsup S et al studied the various causes of bowel obstruction and found adhesions as the most common cause of bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, "small bowel feces sign" is more commonly seen in the matted adhesion [2]. The focal obliteration of properitoneal fat line is also another sign of adhesion [19], which is observed in axial and sagittal reconstruction images. Adhesion may be vascularized and show enhancement in the post-contrast images.…”
Section: Discussionmentioning
confidence: 99%
“…Caoili et al emphasized that the detection and better delineation of the transition zone were possible in coronal reconstruction images [27]. It should be noted that the detection of thin adhesion needs localizing features, such as triangulation of picture archiving and commutating system [19]. Consequently, the multiplanar capabilities of CT make this modality feasible for visibility of the adhesive band, which can improve the surgical outcome and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Достоверность метода составляет от 60 до 96%, специфичность -91%, чувствительность -86%. С этой целью может быть использована компьютерная томография (чувствительность -87,5%, специфичность -92,5%) [6][7][8].…”
unclassified